IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI SMA NEGERI 1 TELUK KERAMAT - Januarti, Agi; Zakso, Amrazi; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the implementation of multicultural education in schools seen from the dimensions of content integration, implementation of multicultural education in schools seen from the dimensions of the knowledge construction process, implementation of multicultural education in schools seen from the dimensions of reducing social prejudice, implementation of multicultural education in schools viewed from the dimensions of justice learning and implementation of multicultural education in schools is seen from the dimensions of school culture empowerment. The approach used is a qualitative approach with a descriptive method. Data collection techniques used are interview techniques and documentation, with a data collection tool in the form of images or photos obtained during the study. Based on the results of research on the implementation of multicultural education in schools it can be seen from 5 dimensions. Keywords: Education, Implementation, , Multicultural